Forensic medical toxicometry of acute carbon monoxide poisoning during alcoholic intoxication - Abdukarimov, B A; Iskandarov, A I (Sudebno-meditsinskaia ekspertiza, 2010)
Data on general toxicity of carbon monoxide (CO) are presented with reference to the gender, age, and the degree of alcoholic intoxication of the affected subjects. Threshold values of carboxyhemoglobinemia for clinical and morphological manifestations of alcoholic intoxication were determined. Expert evaluation of CO toxicokinetics in subjects with alcoholic intoxication revealed informative clinical and morphological signs of carbon monoxide poisoning, the basic parameters of carboxyhemoglobin kinetics, and the sequence of CO-induced clinical and morphological changes during alcoholic intoxication. The data obtained permit to exactly determine the specific cause of death from poisoning with carbon monoxide and ethanol.